The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.31219/osf.io/sd32u
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Visible (Hot) Hand? Expert Players Bet on the Hot Hand and Win

Abstract: Since its inception, the hot hand fallacy literature has tended to focus on whether the hot hand exists, rather than the fitness of hot hand beliefs. We provide the first evidence that people---here experienced practitioners---can profitably exploit their hot hand beliefs. In particular, using the data from the original hot hand field study we find that players' bets predict future outcomes. We use simulations to demonstrate how under-powered tests and misinterpreted effect sizes led the original study to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…In addition, GVT misinterpreted their measures of bettors' ability to predict. In light of these limitations, Miller and Sanjurjo () reanalyzed GVT's betting data, and found that players on average shoot around +7 percentage points higher when bettors have predicted that the shot will be a hit, rather than a miss (p<.001). This increase is comparable in magnitude to an NBA shooter going from slightly above average to elite in three point percentage.…”
Section: Application To the Hot Hand Fallacymentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, GVT misinterpreted their measures of bettors' ability to predict. In light of these limitations, Miller and Sanjurjo () reanalyzed GVT's betting data, and found that players on average shoot around +7 percentage points higher when bettors have predicted that the shot will be a hit, rather than a miss (p<.001). This increase is comparable in magnitude to an NBA shooter going from slightly above average to elite in three point percentage.…”
Section: Application To the Hot Hand Fallacymentioning
confidence: 99%
“…However, in light of the results presented in the present paper, subjects' responses in GVT's unincentivized survey are actually qualitatively consistent with the evidence presented above. More substantively, GVT's statistical analysis of betting data has recently been shown to be considerably underpowered, as the authors conducted many separate individual bettor level tests rather than pooling the data across bettors ( Miller and Sanjurjo ()). In addition, GVT misinterpreted their measures of bettors' ability to predict.…”
Section: Application To the Hot Hand Fallacymentioning
confidence: 99%
“…Recently, a growing body of literature in sports analytics is interested mainly in studying the claims of many coaches, players, and fans that momentum impacts the outcome of the game [2]. These papers often conclude that momentum, as it is traditionally defined, does not exist in team sports [3,4].…”
Section: Introductionmentioning
confidence: 99%